Knowledge, science, and local tradition : multiple perspectives on the moddle East and Southeast Asia in honor of Fritz Schulze - Knowledge,_science,_and_local_tradition... (Harrassowitz Verlag, 2021)
st,1/irh,jil.3,c.1